HUBUNGAN PENGGUNAAN APLIKASI EXAMVIEW DENGAN KEPRAKTISAN PENILAIAN HASIL BELAJAR DI SMKN 4 PAYAKUMBUH - Redha Okta Safitri; Liza Efriyanti; Supriadi Supriadi; Riri Okra (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the evaluation of learning using paper-based tests which are less attractive to students. This is because the question papers distributed are less clear than the colorless photocopies. Teachers are lazy in correcting test answers because correcting them takes a long time. Students must wait until the correction of answers is complete. The results of corrections from the teacher also often make mistakes. The solution to the problem above is the evaluation of learning with the examview application. This application can help teachers to create question banks and conduct assessments automatically. Therefore, this study aims to identify how big the relationship between the use of the examview application and the practicality of the assessment of learning outcomes and the type of research used is quantitative research with a correlation research design. The sampling technique was simple random sampling and the samples taken in this study were teachers at SMKN 4 Payakumbuh. The data collection technique is the distribution of questionnaires using a linkert scale questionnaire. The data analysis technique used is the analysis prerequisite test which consists of normality test and linearity test and hypothesis testing, namely product moment test and simple linear regression test. Based on the results of this study, it was obtained that there was a relationship between the use of the examview (X) application and the practicality of the assessment of learning outcomes (Y). 2%, disagree 3%, disagree 1.8% of respondents and the results of the analysis prerequisite test and hypothesis testing which can be concluded that the two variables have a strong relationship with a positive correlation Keywords: examview, practicality, assessment